Analisis Penurunan Daya Pada Sistem Propulsi Lokomotif Transmisi Diesel Elektrik CC 203 Di Depo Lokomotif - M. Reza Hidayat; Denasti Fajar Sukmawan (Sekolah Tinggi Teknik - PLN, 2020)
Depo Lokomotif is a work unit that is responsible for locomotive reliability in running the railroad transportation operational business. According to internal monthly report data from February 2019 to February 2020, there were 6 cases of weak locomotive power disruptions that caused operational delays. Analysis was carried out on the CC203 locomotive propulsion system in order to obtain the value of the power reduction in one case of disturbance by comparing the output value against the set standard value. Using mathematical calculation methods from the applicable equations and processing the data on MS.Excell. From the results of the study, the cause of the decrease in locomotive power is due to a decrease in the excitation value so that it affects the output value of the Main Generator at each Notch and has an impact on the motor traction power supply also decreases. The Main Generator can only issue a maximum Horse Power at Notch 8 of 1389.96 HP from 1985.31 HP with a decrease of 595 HP. The electric motion of the generator exciter has the largest decrease at Notch 7 of 6.02 volts from 30.48 volts to 24.46 volts. Motor traction can only output a maximum terminal power of 985.067 Watt from 1407 KWatt. The maximum electromagnetic torque of the Notch 8 motor traction is 2855.48 N.m in the series transition and 3070.21 N.m in the parallel transition. Losses on a series transition of 36886 Watts and a parallel transition of 9122 Watts.